2009
DOI: 10.1590/s0100-06832009000200006
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade da produtividade da soja em função de atributos físicos de um latossolo vermelho distroférrico sob plantio direto

Abstract: (2) RESUMO Atualmente, no cenário nacional, a cultura da soja em plantio direto é muito utilizada na integração agricultura-pecuária. No ano agrícola de 2006/2007, no município de Selvíria (MS), entre as latitudes de 20 ° 18 ' 05 " S e 20 ° 18 ' 28 " S e as longitudes de 52 ° 39 ' 02 " W e 52 ° 40 ' 28 " W, foi analisada a produtividade da soja, em plantio direto, em função de alguns atributos físicos de um Latossolo Vermelho distroférrico. O objetivo foi selecionar, entre os atributos do solo pesquisados, aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 19 publications
1
3
0
2
Order By: Relevance
“…Despite the similar GY between NT and MT (Table 1), yields were higher than those reported by Rosa Filho et al (2009), who assessed NT in an Oxisol, and similar to those observed by Girardello et al (2014), who also found no GY difference in Oxisol under NT and a scarified area. The use of scarifiers in planting systems does not always increase soybean yield (Cortez et al, 2017).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Despite the similar GY between NT and MT (Table 1), yields were higher than those reported by Rosa Filho et al (2009), who assessed NT in an Oxisol, and similar to those observed by Girardello et al (2014), who also found no GY difference in Oxisol under NT and a scarified area. The use of scarifiers in planting systems does not always increase soybean yield (Cortez et al, 2017).…”
Section: Resultssupporting
confidence: 81%
“…However, compacted and subcompacted layers emerge as a result of fewer soil operations (Franchini et al, 2011), making it a limiting factor in achieving maximum crop yield (Araújo et al, 2004). With the higher BD, penetration resistance (PR) and microporosity (MI) increase, causing a decline in TP, macroporosity (MA) and hydraulic conductivity (Rosa Filho et al, 2009). Scarification has been adopted to reverse this process, based on the principles of NT (Bertolini & Gamero, 2010;Nunes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As áreas de SPD no entorno dos fragmentos de Mata Atlântica apresentaram maiores valores de Ds, variando de 1,03 a 1,19 Mg m -3 , sendo diferentes dos pontos mais internos dos fragmentos (MR e CF) em todas as camadas avaliadas (Tabela 5). Os maiores valores de Ds em SPD, mesmo com o menor tráfego de máquinas agrícolas, podem ter ocorrido principalmente pela textura mais argilosa, aliada à não adoção de um sistema mais diversificado de culturas (ROSA FILHO et al, 2009), porém Reis et al (2016) verificaram que os valores de Ds diminuem após os sete anos de adoção do sistema. Rosset et al (2014a), no trabalho que avaliou cronossequência de SPD com seis, 14 e 22 anos de implantação na mesma região deste estudo evidenciaram redução de Ds com o aumento do tempo de implantação, em todas as camadas avaliadas.…”
Section: Resultsunclassified
“…According to Rosa (2009), such alteration in soil structure leads to reduction in aeration and water infiltration in the soil, due to the decrease in macroporosity. On the other hand, the increase in microporosity favors the retention of the small volume of water which percolates in the soil profile.…”
Section: Discussionmentioning
confidence: 99%